2016
DOI: 10.1016/s1470-2045(16)00077-2
|View full text |Cite
|
Sign up to set email alerts
|

Dabrafenib in patients with BRAFV600E-positive advanced non-small-cell lung cancer: a single-arm, multicentre, open-label, phase 2 trial

Abstract: Background Activating BRAF V600E mutations are found in approximately 1–2% of adenocarcinomas of the lung offering an opportunity to test targeted therapy for this disease. Dabrafenib is an oral selective inhibitor of the BRAF kinase. The aim of this study was to assess the clinical activity of dabrafenib in patients with advanced BRAF V600E-mutant non-small cell lung cancer (NSCLC). Methods In this phase 2, multicenter, nonrandomized, open-label study of previously treated and untreated patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
279
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(292 citation statements)
references
References 36 publications
7
279
1
5
Order By: Relevance
“…Recently, a phase II clinical trial (no. NCT01336634) has made its results public (16). Dabrafenib exhibited clinical activity in BRAF V600E-positive metastatic NSCLC; these results indicated that dabrafenib could represent a treatment option for a population of patients with limited therapeutic options (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a phase II clinical trial (no. NCT01336634) has made its results public (16). Dabrafenib exhibited clinical activity in BRAF V600E-positive metastatic NSCLC; these results indicated that dabrafenib could represent a treatment option for a population of patients with limited therapeutic options (16).…”
Section: Discussionmentioning
confidence: 99%
“…NCT01336634) has made its results public (16). Dabrafenib exhibited clinical activity in BRAF V600E-positive metastatic NSCLC; these results indicated that dabrafenib could represent a treatment option for a population of patients with limited therapeutic options (16). Certain studies (57-62) have evaluated BRAF mutations in NSCLC samples; however, the use of CastPCR in assessing these mutations has not, to the best of our knowledge, been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutant BRAF promotes tumor growth by hyperactivating the RAF-MEK-ERK signaling cascade (2)(3)(4)(5). BRAF V600E is the most common oncogenic form of BRAF in most tumor types, and selective RAF inhibitors such as vemurafenib and dabrafenib have demonstrated clinical efficacy in melanoma and LA harboring BRAF V600E (6)(7)(8)(9). Despite these findings, ∼15% of BRAF mutant cancers do not respond to BRAF inhibitors, and the majority of patients who achieve a response will inevitably acquire resistance to these targeted agents, predominantly through reactivation of MAPK pathway signaling (4,(10)(11)(12)(13)(14)(15)(16).…”
Section: G466vmentioning
confidence: 99%